2023
DOI: 10.1186/s12944-023-01840-0
|View full text |Cite
|
Sign up to set email alerts
|

Number of recurrences is significantly associated with the post-acute pancreatitis diabetes mellitus in a population with hypertriglyceridemic acute pancreatitis

Abstract: Background Twenty-three percent of patients are diagnosed with diabetes mellitus after the first episode of acute pancreatitis. The incidence of post-acute pancreatitis diabetes mellitus is significantly higher than that of type 1 diabetes mellitus. Some studies have concluded that the all-cause mortality and worse prognosis of diabetes after pancreatitis are higher. We predicted that number of recurrences of pancreatitis would be significantly associated with the incidences of metabolic syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…We observed a near statistically significant increased odds of DM [OR: 1.89; CI: 0.95–3.77; Figure 6A ; ( 4 , 20 , 29 , 35–37 , 41–43 , 50 )] and PD/DM [OR: 1.72; CI: 0.92–3.20; Figure 6B ; ( 23 , 27 , 29 , 33 , 47 )] recurrent acute pancreatitis (RAP) compared to a single AP episode. Subgroup analysis for follow-up length found no effect of time; however, few studies made up each subgroup.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…We observed a near statistically significant increased odds of DM [OR: 1.89; CI: 0.95–3.77; Figure 6A ; ( 4 , 20 , 29 , 35–37 , 41–43 , 50 )] and PD/DM [OR: 1.72; CI: 0.92–3.20; Figure 6B ; ( 23 , 27 , 29 , 33 , 47 )] recurrent acute pancreatitis (RAP) compared to a single AP episode. Subgroup analysis for follow-up length found no effect of time; however, few studies made up each subgroup.…”
Section: Resultsmentioning
confidence: 85%
“…Some studies explored the effect of different numbers of AP episodes. Three or more episodes of AP were associated with a near statistically significant increased odds of DM [OR: 2.53; CI: 0.95–6.74; ( 4 , 20 , 41 )] compared to having one or two AP episodes ( Supplementary Figure S10 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of PPDM-A increases with increasing follow-up time, the number of recurrences, and other clinical factors ( 31 - 33 ). In this study, we found significant differences in the follow-up time and the number of recurrences between the PPDM-A and non-PPDM-A groups in the training and internal validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pancreatitis, the trypsin in the pancreas is activated, leading to edema and bleeding in the tissues around the pancreas, and even produce necrotic inflammatory reactions, which seriously reduces the life quality of patients[ 13 , 14 ]. In addition to clinical treatment, scientific nursing intervention is equally important, while the nursing intervention alone cannot achieve an ideal effect[ 15 , 16 ]. Therefore, on the basis of standardized nursing, more comprehensive and high-quality intervention measures should be taken.…”
Section: Discussionmentioning
confidence: 99%